Reliability of wearable sensors single and dual-task Timed Up and Go test among community-dwelling older women - Yu, Xiao; Dev, Roxana Dev Omar (BioMed Central, 2025)
Background: Approximately one third of community-dwelling older adults fall each year, and older women experience roughly twice the rate and number of falls as men. The timed up and go test (TUG) is a widely used to assess mobility and fall risk. However, its ability to detect subtle gait impairments may be constrained in high-functioning older adults. Objective: This study aimed to evaluate the reliability of gait parameters measured by wearable inertial sensors during single-task timed up and go test (ST-TUG) and dual-task timed up and go test (DT-TUG) in community-dwelling older women, to assess their usefulness for fall-risk screening. Methods: Twenty-five cognitively healthy women (mean age 70.09 ± 3.52 years) completed ST-TUG and DT-TUG within a two-day interval. Wearable inertial sensors yielded 21 parameters, including completion time, spatiotemporal measures, coefficients of variation, and turn-related metrics. Reliability was assessed using intraclass correlation coefficients (ICC), the standard error of measurement (SEM and SEM%), and the minimal detectable change at 95% confidence (MDC95). Results: Gait spatiotemporal parameters demonstrated good to excellent test–retest reliability (ICC ≥ 0.75) under both ST and DT conditions, whereas gait variability and turn-related measures showed poor reliability (ICC < 0.50). Measurement error was slightly higher under dual-task conditions. The DT-TUG appeared more sensitive to gait disturbances relevant to fall risk. Conclusions: Combining wearable sensors with ST-TUG and DT-TUG provides reliable, repeatable measurement of core timing/pace metrics in older women. Although variability and turn-related measures exhibit limited short-interval reliability, DT-TUG may enhance early fall-risk screening when paired with detailed gait analysis.